A data-driven contrastive study on Malay ESL learners’ use of lexical verbs and verb-noun collocations in argumentative writing / Shazila Abdullah - Abdullah, Shazila (Institute of Graduate Studies, UiTM, 2015)
Learner writing is often characterized by linguistic errors, especially in lexical verbs, which can contribute to communicative incompetence. It is also generally known that verb-noun collocations are a characteristic of native writing. The main objective of this thesis is to investigate the linguistic errors made by non-native learners and to suggest ways how they can improve their level of proficiency. Previous studies have looked into the occurrences of either lexical verbs or verb-noun collocations with little emphasis on the phraseology of verb-noun collocations formed from commonly used lexical verbs. Based on these premises, the thesis explores the use of lexical verbs and verb-noun collocations in two learner corpora, one of which is a native learner corpus and the other a specific group of non-native learners, i.e. Malay ESL learners. The data-driven analysis specifically adopted for this study allows for a focus on the most commonly used lexical verbs and verb-noun collocations. Furthermore, an in-depth contrastive interlingual analysis between the corpora of native and non-native learners enables the researcher to uncover the difficulties that learners face in using these lexical items…